Profilo terapeutico e farmacoeconomico di linezolid - Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2004)
The incidence of nosocomial infections from Gram-positive pathogens has been increasing in the last two decades, alongside the development of antibiotic resistance in many bacteria. Glycopeptidic drugs are the most widely used options for these patients, but some bacterial strains with low sensibility to vancomycin and teicoplanin are starting to emerge, warranting careful monitoring and control of nosocomial and also community- acquired infections. This paper outlines a clinical, therapeutic and economic profile of linezolid, the first drug of the only new antibiotic class developed in the last thirty years. In clinical trials, linezolid has demonstrated very promising efficacy and safety in the treatment of antibiotic-resistant infections, in particular those caused by methicillin-resistant staphylococci (MRSA), obtaining greater or equal clinical and microbiological success rates than the standard options. Linezolid, as most newer drugs, has higher acquisition costs than the alternatives, but also bears interesting features that may modify the formation of infection treatment costs. In particluar, linezolid is very well absorbed after oral administration, allowing the planning of sequential iv/os strategies that have the potential to reduce health care costs and to improve the quality of life of the patients by shortening the length of hospitalization. Economic evaluations have demonstrated that this advantage is not merely theoretical, but that it can be achieved in real practice. In particular, linezolid has been shown to be more cost-effective than teicoplanin and vancomycin in the treatment of hospitalized, MRSA-related nosocomial pneumonia and severe infections.